Analysis Of Elderly Health Factors In Preventing Hypertension In Older Age (HEALTH CARE: JURNAL KESEHATAN, 2026)
The elderly population in Indonesia has increased significantly over the past 30 years, reaching 20.7 million (8.2%) in 2014. The elderly are a vulnerable group with physical, mental, and social health problems. This study aimed to examine the age of the elderly, their health problems in the past three months, their health check-ups, their use of traditional medicine, and the condition of their home floors. This study used a descriptive analytical method with a cross-sectional approach. The results showed that the majority of elderly participants were aged 60-69 (54 people) (49.1%), 26 (23.6%) had hypertension in the past three months, 103 (93.6%) had never had a health check-up, 63 (57.3%) always used traditional medicine at home, and 7 (6.4%) families had slippery floors. Based on these results, it is recommended that elderly people be monitored by health workers, their families, and the community through support and motivation. All of this is to maintain their health in old age